Simultaneous enhancement of phenolic compound degradations by Acinetobacter strain V2 via a step‐wise continuous acclimation process. (16th October 2015) - Lin, Johnson; Sharma, Vikas; Milase, Ridwaan; Mbhense, Ntuthuko
Abstract : Phenol degradation enhancement of Acinetobacter strain V2 by a step‐wise continuous acclimation process was investigated. At the end of 8 months, three stable adapted strains, designated as R, G, and Y, were developed with the sub‐lethal concentration of phenol at 800, 1100, and 1400 mg/L, respectively, from 400 mg/L of V2 parent strain. All strains degraded phenol at their sub‐lethal level within 24 h, their growth rate increased as the acclimation process continued and retained their degradation properties even after storing at −80 °C for more than 3 years. All adapted strains appeared coccoid with an ungranulated surface under electron microscope compared to typical rod‐shaped parental strain V2 . The adapted Y strain also possessed superior degradation ability against aniline, benzoate, and toluene. This study demonstrated the use of long term acclimation process to develop efficient and better pollutant degrading bacterial strains with potentials in industrial and environmental bioremediation.